A comprehensive DFT study of physical and photocatalytic properties of Sr1-xCdxTiO3. (December 2022) - Ullah, H.M. Naeem; Rizwan, M.; Zahid, U.; Imran, A.; Cao, Chuanbao
Abstract: Energy production from economic sources is a matter of concern for the last decade. Motivating from this, different properties of pristine and cadmium-induced SrTiO3 are probed using first-principles calculations to predict a material for applications, including hydrogen production through water splitting and optoelectronic devices. Cd substituted at Sr site revealed to be more booming than Ti, as brand new gamma points emerged, impacting the electronic formation of pure SrTiO3 by reducing band gap from 1.78 to 0 eV (GGA) and from 4.326 to 1.68 eV (HSE03). Fermi level shifted to near valence band in Cd substitution, revealing p-type property of semiconductor material. Subsequently, mechanical properties resulting from elastic constants were established, and these materials were finally established to justify the requirements for Born's stability. We evaluated and compared optical properties of pristine SrTiO3 with Cd-loaded SrTiO3, such as refractive index (3.62), dielectric function, and other optical properties. Pristine and Cd-SrTiO3 play a vital role in hydrogen evolution reaction (HER), oxygen evolution reaction (OER), and overall water splitting. The studied materials are claimed to be not only lead-free for green energy applications in photocatalytic activity, but also have a band gap range that is ideal for solar cell applications. Graphical Abstract: ga1